CONTENT AS A GROWTH ENGINE: MANAGING STRATEGY, PRODUCTION, AND DISTRIBUTION AT SCALE - Erlina Desi Purwanti; Lukmanul Hakim; Dahrul Aman Harahap (RADJA PUBLIKA, 2026)
In the digital economy, content has evolved from a marketing tactic to a core driver of customer acquisition, engagement, and revenue. However, scaling content operations effectively presents significant strategic and operational challenges. This study investigates how organizations can systematically manage content as a scalable growth engine. The objective is to develop an integrated framework for aligning content strategy with business objectives, optimizing production workflows, and mastering multi-channel distribution. Employing a qualitative multiple case study methodology, the research analyzed in-depth interviews with 38 content leaders and practitioners across seven high-growth companies. The results identify three critical pillars: a documented strategic